A novel, cell‐permeable, collagen‐based membrane promotes fibroblast migration. (6th May 2018) - Sadeghi, R.; Mahdavi, P.; Lee, W. S.; Quan, B.; Sone, E.; Ganss, B.; McCulloch, C. A.
Abstract : Background and Objective: Growth factors are frequently incorporated into scaffolds to promote periodontal regeneration but many currently used scaffolds do not encourage cell migration towards the dentogingival junction. We examined the proliferation and migration of human gingival fibroblasts in a novel, physically robust, collagen‐Vicryl™ membrane loaded with fibronectin (FN) and/or insulin‐like growth factor (IGF‐I). Biocompatibility of the membranes was evaluated in rat dorsal skin. Material and Methods: Chemotaxis was examined in Boyden chambers and cell migration by confocal imaging of membranes, which were fabricated from rat tail type I collagen with embedded Vicryl knitted mesh, IGF‐I (50, 100 ng/mL) and FN (10 μg/mL). Membranes (Vicryl alone, collagen+Vicryl, collagen+Vicryl+IGF‐I, collagen+Vicryl+FN') were implanted subcutaneously in 8 rats and were evaluated by histomorphometry after 7 and 14 days. Results: IGF‐I (50 or 100 ng/mL) promoted chemotaxis compared with vehicle controls ( P  = .02, P  = .001, respectively). IGF‐I did not affect cell proliferation. Incorporation of FN retarded time‐dependent release of IGF‐I from collagen gels. Three dimensional confocal microscopy imaging of cell migration through collagen+Vicryl membranes showed enhanced migration in the IGF+FN group compared to all other groups at 8, 10 and 14 days ( P  < .05). In a rat skin model, implanted membranes were surrounded by thin collagen capsules and mild inflammatory infiltrates. Conclusion: Incorporation of FN into IGF‐I‐loaded collagen+Vicryl membranes reduced IGF release from collagen and increased the migration of human gingival fibroblasts. The new membrane may promote healing and reformation of the dentogingival junction.